2020
DOI: 10.4269/ajtmh.19-0467
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Orthopoxvirus Circulation in Humans in the Wake of a Monkeypox Outbreak among Chimpanzees in Cameroon

Abstract: Monkeypox virus is a zoonotic Orthopoxvirus (OPXV) that causes smallpox-like illness in humans. In Cameroon, human monkeypox cases were confirmed in 2018, and outbreaks in captive chimpanzees occurred in 2014 and 2016. We investigated the OPXV serological status among staff at a primate sanctuary (where the 2016 chimpanzee outbreak occurred) and residents from nearby villages, and describe contact with possible monkeypox reservoirs. We focused specifically on Gambian rats (Cricetomys spp.) because they are rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 29 publications
(38 reference statements)
0
47
0
Order By: Relevance
“…Additionally, anti-OPXV antibodies were found in several non-human primate (NHP) species in West and Central Africa, while they were absent in large cohorts of wild NHPs in other parts of the world [ 37 ]. In recent years, repeated occurrences of monkeypox outbreak were reported among chimpanzees housed at wildlife sanctuaries in Cameroon and Cote d’Ivoire [ 38 , 39 ].…”
Section: Virus Host Rangementioning
confidence: 99%
“…Additionally, anti-OPXV antibodies were found in several non-human primate (NHP) species in West and Central Africa, while they were absent in large cohorts of wild NHPs in other parts of the world [ 37 ]. In recent years, repeated occurrences of monkeypox outbreak were reported among chimpanzees housed at wildlife sanctuaries in Cameroon and Cote d’Ivoire [ 38 , 39 ].…”
Section: Virus Host Rangementioning
confidence: 99%
“…Nowhere are such risks more evident than in zoological and sanctuary settings, where captive and semi-captive primates come into frequent close contact with people 22 , 23 . For example, contact with New World primates led to simian foamy virus transmission to primate workers in Brazil 24 and monkeypox virus transmission occurred in staff at a primate sanctuary following a monkeypox outbreak in sanctuary chimpanzees ( Pan troglodytes (Blumenbach, 1775)) in Cameroon 25 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted that monkey is the significant host of the monkeypox virus. Other than the monkey, several zoonotic hosts of the virus have been found, such as chimpanzees (Guagliardo et al 2020 ), rodents (Salzer et al 2013 ), prairie dogs (Weiner et al 2019 ), etc. From serologic evidence, it was observed that this virus might transmit from rodents to individuals (Salzer et al 2013 ).…”
Section: The Zoonotic Host Of the Recent Transmitted Zoonosis Of Monk...mentioning
confidence: 99%